Reduced Levels of miR-342-5p in Plasma Are Associated With Worse Cognitive Evolution in Patients With Mild Alzheimer’s Disease - Dakterzada, Farida; David Benítez, Iván; Targa, Adriano; Lladó, Albert; Torres, Gerard; Romero, Leila; de Gonzalo-Calvo, David; Moncusí-Moix, Anna; Tort-Merino, Adria; Huerto, Raquel; Sánchez-de-la-Torre, Manuel; Barbé, Ferran; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Progressive cognitive decline is the most relevant clinical symptom of Alzheimer’s disease (AD). However, the rate of cognitive decline is highly variable between patients. Synaptic deficits are the neuropathological event most correlated with cognitive impairment in AD. Considering the important role of microRNAs (miRNAs) in regulating synaptic plasticity, our objective was to identify the plasma miRNAs associated with the rate of cognitive decline in patients with mild AD. Methods: We analyzed 754 plasma miRNAs from 19 women diagnosed with mild AD using TaqMan low-density array cards. The patients were grouped based on the rate of decline in the MMSE score after two years (<4 points (N=11) and ≥ 4 points (N=8)). The differentially expressed miRNAs between the two groups were validated in an independent cohort of men and women (N=53) with mild AD using RT-qPCR. Results: In the discovery cohort, 17 miRNAs were differentially expressed according to the fold change between patients with faster declines in cognition and those with slower declines. miR-342-5p demonstrated differential expression between the groups and a good correlation with the rate of cognitive decline in the validation cohort (r=-0.28; p=0.026). This miRNA had a lower expression level in patients who suffered from more severe decline than in those who were cognitively more stable after two years (p=0.049). Conclusion: Lower levels of miR-342-5p in plasma were associated with faster cognitive decline in patients with mild AD after two years of follow-up.